2021
DOI: 10.1017/jfm.2021.230
|View full text |Cite
|
Sign up to set email alerts
|

Length scale for the estimation of buzz frequency in the limit of high mechanical blockage in mixed-compression intakes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Moreover, in a study of unignited behaviour caused by subsonic leakages inside a hypersonic inlet at Mach 6 with a throttling ratio of 0 to 0.69, the intake began to exceed Kantrowitz limitations despite being less than the isentropic limits [12]. Researchers suggested that it is vital to analyse shock train oscillations in order to prevent non-ignition intake situations [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a study of unignited behaviour caused by subsonic leakages inside a hypersonic inlet at Mach 6 with a throttling ratio of 0 to 0.69, the intake began to exceed Kantrowitz limitations despite being less than the isentropic limits [12]. Researchers suggested that it is vital to analyse shock train oscillations in order to prevent non-ignition intake situations [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%